Heat transfer mechanism and thermal performance of a channel with square-wing perforated transverse baffles installed: effect of square-wing location - Eiamsa-Ard, Smith; Phila, Arnut; Pimsarn, Monsak; Maruyama, Naoki; Hirota, Masafumi (My University, 2023)
The aim of this study is to report the influence of wing position (h/e) of perforated transverse baffles with square-wings (SW-PBs) on heat transfer rate and pressure drop characteristics in a channel. The channel has a cross-sectional dimension of 15 cm × 4 cm and a length of 60 cm. Two types of baffles: Solid transverse baffles and square-wing perforated transverse baffles, are comparatively tested. The baffle pitch ratio (p/e) is set to 5.0 and remains constant throughout all experiments which encompass Reynolds numbers (Re) of 6000, 9000, 12,000, 15,000, 18,000, 21,000, and 24,000. Square-wings are introduced at four different locations, h/e = 0.92 (highest wing location), 0.83, 0.75, and 0.67 (lowest wing location). The maximum heat transfer rates achieved in channels with SW-PBs at h/e = 0.92, 0.83, 0.75, and 0.67 are 148%, 157%, 166%, and 180% above that of a plain channel, while pressure losses increase by 9.51–10.69, 9.56–10.79, 9.59–10.86, and 9.64–10.99 times, respectively. Experimental results show that square-wings create multiple impinging jet flows and Nusselt number peaks appear adjacent to the rear of the perforated transverse baffles. When compared to solid transverse baffles, SW-PBs cause lower pressure losses and yield higher thermal performance.
Keywords: Channel; Heat transfer enhancement; Multiple impinging jets; Perforated baffle; Recirculation flow; Solid transverse baffle; Square-wing perforated transverse baffle